Mutagenic Effects on the Growth, Reproductive and Yield Parameters of Praecitrullus fistulosus - Rafiq, Muhammad; Khan, Mehreen; Naqvi, Syed Habib Ahmed; Khatoon, Naseem; Dahot, Muhammad Umar (Biological Sciences - PJSIR, 2017)
The aim of this study was to modify the growth, reproductive and yield parameters of Praecitrullus fistulosus by mutagenesis. The seeds of the plant were treated with chemical mutagens including ethidium bromide and colchicine in concentration of (0.05 and 0.10%) and (0.01 and 0.02%), respectively. Seeds were also treated with UV rays at periods of 1 and 2 h and X-rays for 75 KeV at periods of 5 and 10 sec. The growth features were observed at an interval of one week till the 11th week of their growth period. The data showed that seed germination value and lethality (%) of plants were 80 and 75%, respectively and highest in control plants. The time of seed germination (1.6 days) was least in plants treated with X-rays (10 sec). The mutation frequency (80%) was found to be highest in X-rays (10 sec) and colchicine 0.02%. The vegetative growth parameters such as stem length (77 cm), length of leaves (6.6 cm), average number of leaves (36) and leaf surface area (49.6 cm2) was highest against ethidium bromide 0.01%, colchicine 0.02%, ethidium bromide 0.10% and UV rays 1 h, respectively. While the average diameter of stem of control plants was highest (49.6 cm2). The minimum flowering time (31 days) and fruiting time (42.5 days) were observed in ethidium bromide 0.05% and colchicine 0.01% treated plants. The highest number of fruits (4) was observed in colchicine 0.01% treated plants. In conclusion, seeds of P. fistulosus treated with ethidium bromide and colchicine caused positive impact on growth, reproduction and yield attributes as compared to UV and X-rays treatments.